Effect of short-term estrogen therapy on endothelial function: a double-blinded, randomized, controlled trial. (2nd September 2016) - Hurtado, R.; Celani, M.; Geber, S.
Abstract: Objective: To evaluate the effect of short-term hormone replacement therapy with 0.625 mg conjugated estrogens daily on endothelial function of healthy postmenopausal women, using flow-mediated dilation (FMD) of the brachial artery. Methods: We performed a double-blinded, randomized, controlled trial over 3 years. Randomization was performed using computer-generated sorting. All participants were blinded to the use of conjugated equine estrogens (CEE) or placebo and FMD was assessed by a blinded examiner, before and after 28 days of medication. A total of 64 healthy postmenopausal women were selected and randomly assigned into two groups of treatment: 0.625 mg of CEE or placebo. Results: FMD values were statistically different between the groups ( p = 0.025): the group receiving CEE showed a FMD value of 0.011 compared to the placebo group (FMD = −0.082). The two groups were additionally evaluated for homogeneity through the Shapiro–Wilk test in respect to variables that could interfere with endothelial function such as age ( p = 0.729), body mass index ( p = 0.891), and time since menopause ( p = 0.724). Other variables were excluded during selection of the participants such as chronic vascular conditions, smoking, and sedentary lifestyle. Conclusion: Our results demonstrate that the administration of 0.625 mg CEE for 28 days is effective in improving vascular nitric oxide-dependent dilation assessed by FMD of the brachial artery in postmenopausal women. Clinical trial registration: NCT01482416